(untitled) (Research, Society and Development, 2021)
The protocol considers Levine’s principle, regarding energy conservation, structural, personal and social integrity, providing therapeutic support with less stress for high-risk NBs. The research aims to understand the understanding of professionals involved in the systematization of the Minimum Handling Protocol (MMP) and investigate, in the team’s view, the influence of the PMM in the current and long-term life of extreme premature NBs during care, to know how it is constituted the PMM in the institution and describe the professionals’ feelings regarding training for good practices for the proper performance of the method. This is a descriptive research with a qualitative approach. It was carried out with the multidisciplinary team of the Neonatal Intensive Care Unit (NICU), of the Municipal Hospital of Canoas/RS. The professionals interviewed were physicians, physiotherapists, nurses and professionals trained at the technical level of nursing who at some point used the PMM in extreme or high-risk NBs. Data collection took place through a semi-structured interview with five open questions, which formed the pre-categories: constitution of the PMM in the institution, short-term and long-term benefits, training to perform the minimum handling. The exclusion criteria were the professionals from that hospital who refused to participate or were absent. The main benefit found in the work was the prevention of cranial hemorrhage through the PMM and the low photo stimulus, however, the index was found to be below the necessary training for the team. The present work was approved by the Ethics Committee under opinion nº 3.361,742 and CAAE 09495519.4.0000.5349.